Assimilation of China's rural-to-urban migrants: A multidimensional process. (April 2018) - Chen, Zhenxiang; Liu, Kayuet
This study explores the multidimensional process of assimilation in rural-to-urban migration in China. We distinguish between (a) intrinsic acculturation—the adoption of values; (b) extrinsic acculturation—the adoption of observable traits such as language; and (c) structural assimilation—the achievement of socio-economic status comparable to that of locals. Cross-provincial analysis shows that there are substantial variations in the social and economic distances faced by migrants across provinces. Our novel acculturation/assimilation measures take into account the different cultural and socioeconomic distances faced by migrants with heterogeneous places of origin and destinations. Hypothetical measurement errors are used in a robust hierarchical regression analysis to assess the potential effect of self-selection. Analyses of the Chinese General Social Survey 2012–2013 show that extrinsic acculturation typically takes place later than structural assimilation, while intrinsic acculturation can fail to happen despite a long stay. Assimilation is not guaranteed; only some rural-to-urban migrants, particularly those with high levels of education, from families of high socio-economic status, and interacting with friends and neighbors, manage to assimilate across all three dimensions.